MANAGEMENT OF PERSONNEL DEVELOPMENT PROCESSES AT ENERGY COMPANIES BASED ON THE PROJECT APPROACH - Станьковська, Ірина; Яців, Уляна Володмирівна; Станьковський, Тарас Володимирович; Голубовський, Олег Зіновійович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2023)
The purpose of the study is to manage the processes of personnel development of energy enterprises on the basis of the project approach. The goals of the research are: analysis of the state of the energy industry and its development priorities; analysis of the prerequisites for the development of personnel of energy enterprises in modern conditions; determination of strategic directions of development of personnel of energy enterprises; application of the project approach to the development of the company’s personnel; determination and justification of the need for the development of the company’s personnel; formation of a management model for the personnel development process. In order to solve the investigated problem, the methods of analysis and synthesis, Delphi, the analytical method and the method of scientific generalization were applied. In the process of research, the state of the energy industry of Ukraine was analyzed, the main directions of its further development, specified in the Project of the Recovery Plan of Ukraine, were considered. A study of the state of the personnel of the JSC «Prykarpattiaoblenergo» energy enterprise was conducted using a SWOT analysis. On the basis of the SWOT-analysis and the SWOT- matrix, a priority strategy for personnel development was selected. To ensure the effectiveness of the personnel development process and to determine the need for professional competencies, the personnel certification technology was used. A comprehensive evaluation of management personnel is offered, which makes it possible to evaluate the work of each executive from the standpoint of his performance of operational and strategic activities based on the use of quarterly and annual evaluation. Personnel evaluation is proposed to be carried out using a criterion approach and determining the effectiveness of processes. Personnel development at the enterprise is proposed to be implemented through individual personnel development projects. For the implementation of the personnel development project, a model for managing the personnel development process was developed and the stages of its implementation were determined.